HORROR FILMS IN UNCONSCIOUS ANTHROPOLOGICAL STRATEGIES OF BIOPOWER - S. A. Malenko; A. G. Nekita (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The article is devoted to horror films as forms of anthropological crisis in mass culture, which generate specific meanings and are presented in ways of control over consumer society, as well as act as unconscious ideological mediators of multiculturalism and globalization. Theoretical basis. The main working tool for the analysis of horror films is the method of historical amplification, developed by C. G. Jung, as a basis for comparative analysis of symbolic interpretations of cultural realities and traditions of American horror films. On this basis, the authors propose their own methodological strategy for the analysis of horror films, complementing the theoretical potential of Jungianism with methodological developments of Marxism and neo-Marxism, which can be called "Jung-Marxism". It is distinguished by the orientation and content of socio-cultural phenomena, the essence of which is considered in the context of the interaction of social and archetypal meanings of life of man and society, as well as allows to identify latent unconscious trends in the emergence and functioning of social institutions. With this approach, horror films are not only institutes of production and introduction of fear in consumer society, but also the biotic basis of management at all levels of social communication. Originality. Horror films have a significant impact on the consumer society on the basis of a special mythology, in which the manipulative and propaganda methods of formation and transmission of modern power are sublimated. And the emergence of the horror film genre in American and world cinema means abandoning the model of classical political power based on the sacralisation and rationalization of personal authority and physical coercion. The scientific reflection on the films of this genre allows us to understand the biotic mechanisms of manipulation of social space and the formation of the state of biopower as a new qualitative state of social control. Conclusions. The anthropological model of horror films is concentrated in the following maxim: fear consumes a man a man consumes fear, and the biopower consumes all the subjects of fear consumption, and all their socio-cultural context of communication. Therefore, horror films are a productive means of ideologue-propaganda infection, subsequent deformation and consumer substitution of the mental nucleus of other cultural traditions.